Molas Baju Wara: Hybridity in Manggarai Rap Music - Ans. Prawati Yuliantari (Soegijapranata Catholic University, 2016)
Rap music which has been popular since 2007 in Manggarai region, East Nusa Tenggara, Indonesia, gave rise to rap hybrid phenomenon. The mixture between American rap music formats and local elements of Manggarai attracted the attention of young people in the region. One of the local songs that feature hybridity in rap Manggarai is